LEGAL REGULATION AND IMPLEMENTATION OF THE STATE LANGUAGE POLICY OF THE SLOVAK REPUBLIC ON HUNGARIAN AND UKRAINIAN MINORITIES - Kovalyova , Tetyana (Theory and Practice of Public Administration, 2020)
The purpose of the article is to study the legal regulation and status of the linguistic rights of Hungarian and Ukrainian national minorities in Slovakia. The issues of language policy regarding national minorities in the last years have been investigated by: A. Virostkova, N. Kichera, O. Lopushanskaya, E. Popok, O. Timon, V. Fedonyuk, and other. Today Slovakia is a linguistically homogeneous country. The largest national minority of Slovakia is Hungarian, one of the smallest is the Ukrainian minority. Hungary pursues an active (and sometimes aggressive) policy to protect the linguistic rights of its minorities, often interfering with the laws of other countries. According to the European Charter for Regional and Minority Languages, the Hungarian language has more areas of application than other national minority languages. Ukraine is passive in securing the language rights of the Ukrainian minority in Slovakia, both politically and financially, so at the end of the twentieth century it started assimilation processes of the Ukrainian national minority took place in Slovakia. The lack of interest on the part of Ukraine by its diaspora in Slovakia, the organization of social, economic and cultural activities to support and develop and develop Ukrainians, the state language policy deepened the assimilation of Ukrainians with the autochthonous population – Slovaks and the separation of Ruthenians into a separate ethnic minority. The problem of securing the linguistic rights of Ukrainians in Slovakia is the lack of their self-identification – attributing themselves to Ruthenians or Ukrainians, the non-prevalence of the Ukrainian language, especially written, instead of creating a Russian language that is not recognized by linguists as a dialect of Ukrainian dialects. The adverse situation is also exacerbated by a rational but unacceptable approach in this case to the distribution of public funding depending on the number of minority representatives, which may adversely affect not only their national consciousness and sense of self-worth, but also the development of their mother tongue and education. The financing of the Ukrainian national minority of Slovakia by Ukraine, for example, in the framework of bilateral agreements between countries, when the funds will be allocated for specific activities (for example, printing of textbooks, opening preschools for Ukrainian children, etc.) will be absolutely fair.